Die Ängstlichkeitsskala als Indikator persönlichkeitsspezifischer Regelsysteme im semantischen Gedächtnis - Gerda Lazarus-Mainka; Wrobel, Heike; Michael Kerres (Diagnostica, 1989)
Tested the hypothesis that Spielberger's anxiety scale is an indicator of personality-specific systems of rules stored in semantic memory. For this purpose, dependency relationships between anxiety and the usual criteria for analyzing semantic memory were experimentally measured. These criteria were: degree of intensity, typicality, the U-shaped relationship between intensity and decision time, and intrusions. In conjunction with the administration of the State-Trait Anxiety Inventory, the 84 subjects were asked to describe themselves using 60 adjectives, by means of a nine-step scale. Decision time was measured simultaneously. Finally, the subjects had to name the adjectives they could still remember. The results broadly supported the hypothesis. High and low anxious people differed in the intensity of their attributions of adjectives according to the contents of the words (typicality effect) and in type of intrusions. There was a quadratic trend in the relationship between decision-speed and intensity of attribution. The results were taken to indicate that anxiety is manifested not only in a specified interaction with language, but that the specific relationship with language can also have characteristic systems of rules constituted in semantic memory, which are capable of representation in an anxiety scale.